BUDAYA HUKUM NOTARIS DALAM MENJALANKAN JABATAN - Basyarudin Basyarudin (Fakultas Hukum Universitas Muhammadiyah Palu, 2021)
Notary has role to help society in creating legal certainity and protection. However, nowadays, some Notaries tend to forget their role and responsibility as a Notary and more oriented to money rather than their duty. Thus, this research aims to know how legal culture of a Notary in doing his duty. The research methodology is qualitative using juridical normative approach in which the data gathered by analyzing theories, concepts, fundamentals and constitution related to the problem. The result showed that there are two categories; internal and external. Internal legal culture refers to the Notary’s job in making the deed and service to society, while external legal culture is the society’s responses toward the service given by Notary. Legal culture of Notary becomes the standard in doing the job or known as pattern for behavior. Therefore, it can be concluded that there are some factors that affect the legal culture of Notary, such as the culture in becoming the one and only winner, the culture in bidding the honorarium, and the culture in taking advantage of weakness of Notary. Key Words: Notary, Legal Culture, Deed